The influence of salt reduction with encapsulated oleoresins on the quality of mayonnaise, mustard, and ketchup - Serrano, Carmo; Sapata, Margarida; Castelo-Branco, Diogo; Tasso, Ana; Marques, António; Viegas, Cláudia; Figueira, Diogo; Komora, Norton (Frontiers in Nutrition, 2024)
Introduction Mayonnaise, mustard, and ketchup are table sauces enjoyed worldwide, adding flavour and texture to many dishes. However, these products often contain high sodium content, which contributes to health issues such as high blood pressure and cardiovascular disease. To address these concerns, reducing salt content in the sauces has become a significant goal for both manufacturers and consumers. Objectives This study investigates the effects of three formulations of microencapsulated (ME) oleoresins (F1, F2, and F3), derived from aromatic plants and spices, on the mineral content, physical–chemical properties, colour, and sensory profiles of mayonnaise, mustard, and ketchup. Results The addition of ME ingredients resulted in significant reductions in salt content across all sauces, with reductions up to 50% in mayonnaise, 45% in mustard, and 52% in ketchup, aligning with EU sodium guidelines and allowing for a “reduced Na/NaCl content” nutrition claim. Potassium levels in mustard and ketchup were sufficient to support health claims related to blood pressure maintenance, while chloride content was reduced in ME formulations, better aligning with dietary reference values. Physical–chemical analysis revealed that ME ingredients had minimal impact on parameters like pH, lipid oxidation, and viscosity, although significant differences were observed in specific areas, such as the consistency of ketchup and chloride content in mustard and ketchup. The use of inulin, as a carrier agent, helped maintain the sauces rheological properties. Mustard showed the most similarity to the control in terms of physical–chemical parameters. Colour analysis indicated minimal changes in mayonnaise, moderate changes in mustard, and significant differences in ketchup, particularly with the ME-F3 formulation, where the light-yellow ME ingredients had a pronounced effect on the darker sauce. Despite these differences, the sensory analysis demonstrated that the overall sensory profiles of the ME formulations were similar the like control for all sauces. Mayonnaise showed the closest resemblance, while mustard had slightly lower scores in flavour and saltiness. Ketchup followed the same trend as mayonnaise, with no significant sensory differences compared to the control. Conclusion These findings suggest that ME ingredients can be effectively used in condiment reformulation to achieve significant salt reduction without compromising sensory qualities, while also supporting health-related claims. By incorporating ME-based salt reduction strategies and exploring low-sodium alternatives, consumers can continue to enjoy their favourite sauces while minimising sodium intake. Embracing these changes not only benefits personal health but also aligns with the industry’s commitment to offering more nutritious options.